Shift Work Disorder and Mental and Physical Effects of Shift Work - Pinar Guzel Ozdemir; Anil Cemre Okmen; Onur Yilmaz (Psikiyatride Güncel Yaklaşımlar, 2018)
With the growing prevalence of shift work all over the the world, the relationship between the daily lives of irregular lifestyles and rhythms is being investigated for those working as shift workers and their families. The effect of shift work on physical and mental health is a very important field of research in recent years. The onset and persistence of medical complications in shift workers includes impaired synchronization between work schedule rhythms and circadian clock. In this context, studies have been carried out showing the increased risk of sleep-wake disorders, gastrointestinal problems, and cardiovascular diseases. There is little information about the actual frequency, effect on health and treatment of shift work disorder, known as circadian rhythm sleep disorder. Shift work disorder includes insomnia and/or excessive sleepiness related with the work schedule. The aim of this rewiev, mentioning about the physical and mental effects of shift work, and to provide information about the diagnosis, clinic and treatment methods of shift-work disorder.